Rapid molecular identification of necrophagous diptera by means of variable-length intron sequences in the wingless gene. (May 2018) - Federico, Concetta; Lombardo, Debora; La Porta, Noemi; Pappalardo, Anna Maria; Ferrito, Venera; Lombardo, Francesco; Saccone, Salvatore
Abstract: The arrival of arthropods at a corpse exhibits specific temporal patterns, and Diptera play a key role in the initial stages of the decomposition process. Thus, the correct species assignment of the insect larvae found on a decomposing body is an important step in forensic investigations. Here, we describe a molecular procedure to define the species at larval age found on a corpse more quickly and easily than current systems. Our method involves a unique PCR amplification of a DNA segment within the evolutionarily conserved wingless gene, involved in embryo development. The amplified DNA segment contains the fourth intron of wingless, which we found to be variable in length, from about 800 to 3000 bp, among species of necrophagous Diptera. The identification of the amplified segment size in species from Lucilia, Calliphora and Sarcophaga genera, allowed us to determine the species at larval age collected in the early stages of a decomposing body, with a simple PCR amplification and subsequent electrophoresis. This procedure may help in forensic investigations to estimate the minimum Post Mortem Interval (PMI-min) of a body colonized by these larvae, avoiding the use of time-consuming and/or more expensive procedures. Graphical abstract: Image 1 Highlights: Larvae of necrophagous Diptera are rapidly identified by PCR and electrophoresis gel. Intron-4 of wg gene has a constant intraspecific size that is different between species. A forensic DNA marker could be used for the first step in the evaluation of the PMI-min.